Mapping and Redesign of Administrative Processes with BPM and User Journey: An Experience Report for Digital Transformation - Assis, João Victor C. T. de; Vieira, Larissa Cardoso; Ribeiro, Ana Regina Bezerra; Sobral, Marcos; Oliveira, Renata; Felix, Rafaela Mariane de Lima; Melo, Eduardo Henrique Pereira de; Marinho, Marcelo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Companies’ Digital Transformation (DT) intensified during the Covid-19 pandemic, involving the digitization of processes and cultural adaptation for continuous innovation, increased productivity, and service quality. The interaction of people, procedures, and technologies is crucial in this process. Problem: Traditional organizations with rigid cultures rely on outdated procedures, hindering the adoption of more efficient work practices. Solution: This research explores the use of the Business Process Management (BPM) life cycle to improve three processes in a Brazilian company, integrating user journey to improve processes towards DT. IS Theory: This study is carried out under the Socio-Technical Theory, examining the interaction between people, processes, and technologies to achieve balanced and effective digital transformation. Method: This exploratory research carries a qualitative experience report of the mapping and redesign of business processes of a countryside unit from "Alpha", a Brazilian vocational education organization. Summary of Results: Three financial processes were mapped, analyzed, and redesigned with the use of BPM and user journey map. The improvement proposals were based on the problems and opportunities identified in the processes. Changes in systems and innovative actions were proposed within the company to enhance process efficiency and agility through digital transformation. Contributions and Impact in the IS area: This study reports one execution of a BPM process integrated with user experience techniques aimed at DT. Through the lens of the Socio-Technical Theory, the research presents steps taken into the mapping, analysis, and redesign of processes contributing in similar contexts for both practitioners and researchers in the Information Systems (IS) field.